A Life‐Cycle Cost Analysis of Synthetic Infill and Natural Grass Systems. Issue 1 (19th October 2017) - Daviscourt, Brian L.; Kowalewski, Alec R.; Lambrinos, John G.; Eleveld, Bartelt
Abstract : The perception of a long‐term cost advantage of synthetic infill turf systems relative to natural grass systems has contributed to a rise in their popularity in the United States. This case study compared the costs associated with installation and maintenance of third‐generation synthetic infill and natural turfgrass systems in the US Pacific Northwest. Installation costs, maintenance budgets, and field use information were gathered from five synthetic and five natural grass systems and used to find the cost of providing an hour of use. Costs were inflated by 3% each year and brought back to their present value with a 4% discount rate. For maintenance and replacement scenarios with different planning lives (i.e., 16 vs. 20 yr), net present values were converted to annual equivalents by amortizing the net present values into an annual equivalent payment using the discount rate. Findings from this work determined that the average cost of installing a synthetic field was US$163.00 m −2 and the average annual equivalent was $20.10 m −2 . The average cost of installing a natural grass field was $45.60 m −2 and an annual equivalent $10.10 m −2 . When the cost of providing an hour of use was taken into consideration, the synthetic fields averaged $3.30 per player use hour, and natural grass fields averaged $3.50 per player use hour.